Soybean in Crop Rotation with Maize and Palisade Grass Intercropping Enhances the Long-term Effects of Surface Liming in No-till System - Bossolani, João William [UNESP]; dos Santos, Fabiana Lopes [UNESP]; Meneghette, Hugo Henrique Andrade [UNESP]; Sanches, Izabela Rodrigues [UNESP]; Moretti, Luiz Gustavo [UNESP]; Parra, Lucas Fenelon [UNESP]; Lazarini, Edson [UNESP] (Springer Nature, 2021)
Tropical and subtropical soils are characterized by low natural fertility. Therefore, further research needs to be undertaken to increase surface liming efficiency, improve soil quality, and promote crop development. The low solubility of lime has hampered acidity correction in deeper layers, particularly if a no-tillage system is used. However, surface liming efficiency can be improved if efficient crop rotation programs are implemented. Therefore, the main aim of this study was to investigate the long-term effects of lime doses on soil fertility and the cascading effects of these changes in soybean nutrition and productivity after maize monocrop or intercropped with palisade grass during three growing seasons. In a long-term experiment (started in 2019), soybean was cultivated under four lime doses (0, 2000, 4000, and 6000 kg ha−1) applied to soil surface in two crop systems (after maize monocrop or intercropped maize with palisade grass) during three consecutive agricultural years (2016–2019). Liming reduced soil acidic parameters and increased P, Ca2+, Mg2+, and S–SO42− availability down the soil profile, which improved soybean nutrition and grain yield, particularly when it followed intercropped maize. Intercropping exploits species complementarities, which results in increasing the effectiveness of surface liming under no-tillage systems, contributing to higher soybean yields in crop rotation.
Keywords: Crop rotation; Glycine max L. Merrill; No-tillage system; Soil acidity correction; Urochloa brizantha